Roles of cytokines in modulating Trypanosoma brucei rhodesiense infection outcomes in vervet monkeys - Jebet, Clarah; Thuita, John Kibuthu; Masiga, Daniel; Orindi, Benedict Owino; Oidho, John; Field, Mark C.; Matovu, Enock; Adung’a, Vincent Owino (Frontiers in Parasitology, 2026)
IntroductionHuman African trypanosomiasis (HAT), caused by Trypanosoma brucei rhodesiense, is categorized as acute due to rapid disease progression but presents varying clinical outcomes. Although the mechanisms underpinning differential clinical progression are poorly understood, both host and parasite factors are implicated. Therefore, we sought to elucidate roles of primate host factors in mediating varying T. b. rhodesiense infection outcomes. MethodsHere, we assessed the roles of selected host cytokines in disease progression using a tsetse-mediated infection in a non-human primate (NHP) vervet monkey model that closely mimics HAT and natural infection. We quantified eight cytokines, including TNF-α, IFN-γ, IL-10, IL-6, IL-12, and IL-1β, as well as the brain injury biomarker S100b and clinical data, and compared acute and chronic infections. In addition, ResultsMonkeys infected with KETRI 3801 and KETRI 3928 had mean survival times of 28 and 95 days, respectively. In both infected groups, cytokine levels were significantly higher than those in uninfected controls (p < 0.05). IL-12, IL-6, and IL-1β cytokines were significantly elevated (p < 0.05) from early-stage disease to the onset of late-stage disease. IL-1β, IL-6, IL-12, and IL-10 are implicated in pro- and counter inflammatory responses. In addition, cerebrospinal fluid parasite and white blood cell levels were higher in KETRI 3801 infections compared with KETRI 3928 infections. DiscussionWe conclude that cytokines play roles in modulating disease progression and severity in an NHP model of HAT, which is important for understanding varying infection outcomes.